Horticultural databank - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Fieldworkers, researchers and documentation centres can now make requests to the databank of the Horticultural Crops Group of the FAO for information on high yielding varieties of fruits, vegetables, root crops or tubers. Such information can be...